Maritime Accidents: Technology Links to Casualty Investigation and Risk Management - Fuenzalida López, Manuel (Revista de Marina, 2025)
The shipping industry is rapidly evolving to new technologies and even autonomous vessels. Therefore, new safety challenges have emerged, and the human factor plays new roles in risk assessment and mitigation. Moreover, accident investigation has been a tool for learning lessons and correcting processes, but historically, those corrections have resulted from significant accidents. This academic essay critically analyzes the relationships between Maritime Accidents, Technology, and Casualty Investigation based on risk management with a proactive approach toward the future.